Lead preconcentration by solid phase extraction using oxidized carbon xerogel and spectrophotometric determination with dithizone - Maratta Martínez, Sergio Ariel (2016)
The proposed methodology is based on the preconcentration of Pb2+ on oxidized carbon xerogel, a porous material of low density and high surface area. Adsorbed Pb2+ was eluted with HCl, followed by complexion with dithizone in ethanol-water solution and determined by UV-visible spectrophotometry in a continuous flow system (FI). Variables such as pH, type of eluent, eluent concentration, type of complexing solvent, concentration of complexing reagent and flow rates were optimized. The proposed system reached an enrichment factor of 50, with 5 mL of sample. Detection limit was of 0.9 μg L-1, with a precision of 7.8% (n = 10). The proposed system was successfully applied to the determination of Pb in tap water from San Juan City, Argentina.